2015
DOI: 10.1080/17441692.2015.1030684
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence and forced migration during pregnancy: Structural constraints to women's agency

Abstract: Little is known about migration during pregnancy related to intimate partner violence (IPV). In this paper, we examine issues of agency in relation to pregnant women’s migrations in a high HIV prevalence area of Kenya. We qualitatively explored forced migration among pregnant women, using data from in-depth interviews, focus groups, and IPV screening forms. To quantitatively examine migration during pregnancy, we analyzed data from a prospective study of 614 pregnant women. The qualitative data revealed that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…According to the current state of research, this is regarded as good practice in gender-sensitive epidemiology [ 14 , 17 , 19 ]. Given the relatively rich body of qualitative literature on gender norms [ 48 ] and the intersection of gender and migration [ 49 52 ], and the call for more theory-informed research in quantitative epidemiology integrating the social contexts, we decided to focus on quantitative epidemiologic research only to assess the status quo for this particular field.…”
Section: Methodsmentioning
confidence: 99%
“…According to the current state of research, this is regarded as good practice in gender-sensitive epidemiology [ 14 , 17 , 19 ]. Given the relatively rich body of qualitative literature on gender norms [ 48 ] and the intersection of gender and migration [ 49 52 ], and the call for more theory-informed research in quantitative epidemiology integrating the social contexts, we decided to focus on quantitative epidemiologic research only to assess the status quo for this particular field.…”
Section: Methodsmentioning
confidence: 99%
“…In this “post-socialist” era, male identity, now intrinsically linked to the ability to generate income, faces challenges in the form of humiliation, shame, trauma, failure, or lacking recognition, symbolic forms of violence that can generate an aggressive response (Chodorow 2002; Turan et al 2016). Connell (2005) uses the term “protest masculinity” to describe a masculinity that lacks the resources to reproduce the hegemonic model and so seeks alternative, often violent, sexual, or illicit means of imitating the power that sustains the hegemonic model.…”
Section: A Political Economy Of Masculinitiesmentioning
confidence: 99%
“…In previous studies conducted among PLHIV in this region, food insecurity was widespread (Nagata et al, 2012), and up to 34% of men and 25% of women were found to be underweight (Nagata et al, 2013). A number of gendered structural drivers of HIV risk have been observed in Nyanza, including female labor migration and the exchange of fish for sex in the lake ecology (Camlin, Kwena, & Dworkin, 2013; Camlin, Kwena, Dworkin, Cohen, & Bukusi, 2014), women’s economic disempowerment and property rights violations (Dworkin et al, 2013; Lu et al, 2013), and gender-based violence (Hatcher et al, 2013; Turan et al, 2011, 2015). …”
Section: Methodsmentioning
confidence: 99%